Factibilidad para la carrera de una empresa dedicada a la fabricación de rompopes saborizados en el cantón Bolívar - Solórzano Alcívar, Mercedes Elizabeth (2014)
This work was carried out in the city of canton, Bolívar being the main objective to determine the feasibility for the creation of a company dedicated to the production of flavored rompopes sock. The techniques used in research study of market, the technical study and economic analysis - financial. With regard to the methodology applied frontier research that allowed to know market the product, skills and consumers, likewise descriptive research which removes the features of the niche market and identifies the tastes and preferences of the consumer, the instrument used was the field study which facilitated the collection of information to carry out the survey, which was applied to the inhabitants of the five selected cantons: Bolivar, Chone, Portoviejo, Manta and del Carmen, making in this way the market study determining the demand and supply of eggnog. Population growth rate of projection method was used to establish the percentage of total population growth. Developed a technical study that revealed information of investment and production costs, others ran the financial economic evaluation for the viability of the project. Because the country is very productive born entrepreneurs in productive business ideas. One of the main goals of the company is to provide a quality product with different flavours to suit all tastes, thereby establishing a business that generates jobs and strengthen the development of the country, province and canton.